Na vibe das mulheres DJs: sentimento, mixagem e subversão - Sucena Junior, Edson (2017)
This dissertation it is proposed to understand how the process of construction of identities of women DJs in the scene GLS in Goiânia, from the point of view that the DJ's are performers in the musical, as it cut through the mix, the relationship with the music and creating, they have the power to bring the crowd to ecstasy and trance in the club scene. This is a study about the narrative of women who act as professional DJs who now approaching, now distance themselves with regard to musical styles, because each one has its identity in the construction of his sets and in their performances. By understanding that identity is a social and cultural construction, we are led to think and problematize notions such as “feeling” (sensation), subversion and performance. These are women who are in their subordinate modes of being and expressing ourselves in the world while the genre and artists on the margin, in spaces with strong markers of social difference. Bring the voices of these women means enhancing movements and shifts of identity that will put you in check the heteronormativity compulsory. Is it so that this “feminine plural” starts to be questioned in their becomings and multiplicities. Therefore, to interrogate these identities allows us to question: a DJ is performance? How to build a DJ? Can the DJ talk? Performances and performatividades bypass their identities? Therefore, listening to the narratives of these women and go through their intimate allows us to create conditions and possibilities to which the subaltern can indeed speak and show their you can actually talk and show their potential subversive.